Workplace Environment and Its Effect on Employee Productivity: Insights from the Boyolali Garment Industry - Anugerah, Adhe Rizky; Mahmud , Dyantika Putry; Jayatri , Ummi Fakhriyah; Wijayanti , Nanik; Nanda , Syalfa Oktifa; Jinan , Shannaz Fairuz Nurul (Tekmapro, 2025)
This study aims to analyze the influence of physical and non-physical work environments on employee performance in the garment industry. Both physical and non-physical work environments are crucial factors that affect employee productivity and well-being. The research method employed is a survey with a Structural Equation Modelling (SEM) approach to evaluate the relationships between latent variables, namely physical work environment, non-physical work environment, and employee performance. Data were collected through questionnaires distributed to 39 respondents working in a garment company in Boyolali, Central Java. The analysis results show that the physical work environment has a significant influence on employee performance, with aspects such as temperature, ventilation, noise, and workspace layout contributing positively. On the other hand, the non-physical work environment, such as communication with superiors, self-development, and responsibility, does not show a direct significant effect on employee performance. These findings indicate that improvements in physical aspects are more urgently needed to directly enhance employee performance. However, non-physical factors may require a more strategic and in-depth approach to yield optimal impact.